Survey on Efficient Use of Spatial Reusability in Multhop Wireless Network - Murugaveni, S; Mahalakshmi, K (International Journal of Engineering and Technology, 2018)
The present wireless routing protocols does not increase the end-to-end throughput by reducing the number of hops to deliver a single packet from a source to a destination node. To maintain the proper link among the nodes in multihop wireless ad-hoc networks, the medium access control (MAC) protocol plays a vital role. The spatial reuse and throughput of a multihop network is greatly affected in assessing the level of interference, channel sharing was not expeditiously utilized by the prevailing methodology of the IEEE 802.11.Routing protocols are generally depends on transmission cost, minimizing routing metrics. But they fail to give assurance for increasing end-to-end throughput. The existing protocols don't take spatial reusability of the remote correspondence media into account. This paper overviews numerous techniques to upgrade the effective channel use by enhancing the spatial reuse.